Are child health information services a viable source of accurate vaccination data for clinicians working in paediatric emergency departments in England?. Issue 1 (23rd December 2021) - Isba, Rachel; Davies, Nigel; Knight, Jo
Abstract : Vaccination is a global success story, yet UK coverage remains undertarget for a number of diseases. The paediatric emergency department (PED) offers the potential for opportunistic vaccination interventions. Objectives: To map the Greater Manchester (GM) Child Health Information System network to see if it was a viable source of vaccination data for clinicians working in the PED as a case study. Methods: Postprimary care vaccination management systems for GM were visualised using a systems mapping approach, with data obtained from the Office for National Statistics and commissioners in the GM Health and Social Care Partnership. Results: Once vaccination data left primary care, it passed through 1 of 10 local child health information services (CHISs), using an assortment of different information technology systems, after which it shed individual identifiers and was aggregated within national systems. None of the existing GM CHISs were accessible to PED practitioners. Conclusion: More work needs to be done to explore possible alternative sources of accurate vaccination data during a PED consultation.